SEVERAL ISSUES OF PRODUCTIVITY INCREASE AND ECONOMIC EFFECTIVENESS OF HYDRAULIC PERFORATED HAMMER OF CYCLING CAPACITY - V.I. MIRNY (Advanced Engineering Research, 2008)
The work covers the issues of productivity increase and economic effectiveness of hydraulic circuit hammer through changes of constructive and functional parameters.